Are patients with Parkinson's disease at a lower risk of catching the common cold? Propensity score matching. (January 2023) - Neshige, Shuichiro; Aoki, Shiro; Nezu, Tomohisa; Nakamori, Masahiro; Yamazaki, Yu; Ohshita, Tomohiko; Maruyama, Hirofumi
Abstract: Introduction: Accumulating evidence indicating that inflammatory responses play crucial roles in Parkinson's disease (PD) development provided a hypothesis that physiological alpha-synuclein may contribute to inflammatory responses against infections during non-advanced stages of PD. Thus, we examined the risk of catching a common cold in patients with PD as compared to other common brain diseases. Methods: We extracted PD (non-advanced; without dementia) and control (AD: Alzheimer's disease, migraine, epilepsy, and ischemic stroke) patient data from insurance claim data available between 2010 and 2021. After confirming the clinical PD diagnosis, we investigated factors associated with cold diagnoses and used propensity score matching to identify differences in the incidence of colds between PD and control patients. Results: Diagnosis of colds in PD patients (n = 726) and controls (AD = 377, migraine = 1019, epilepsy = 3414, ischemic stroke = 6943) was found in 1186 (9.5%) patients, which was independently associated with being female (odds ratio: OR 1.59; 95%CI 1.41–1.79; P < 0.0001), follow-up by neurologists (OR 1.30; 95%CI 1.15–1.48; P < 0.0001), diagnosis of PD (OR 0.30; 95%CI 0.20–0.45; P < 0.0001) and COVID-19 pandemic period (OR 0.58; 95%CI 0.47–0.72; P < 0.0001). After propensity score matching, the incidence of colds was significantly lower in PD (3.4%) versus in controls; AD (9.8%; P < 0.0001), migraine (13.3%; P < 0.0001), epilepsy (11.0%; P < 0.0001), ischemic stroke (8.8%; P < 0.0001). Conclusions: Patients with PD were less likely to be diagnosed with colds. However, several confounding factors will need to be examined. Moreover, alpha-synuclein may provide protective resistance to viral infections by activating the immune system due to chronic inflammation in non-advanced PD patients. Highlights: We evaluated the association between PD and risk of common colds. We used a propensity score to compare patients with PD with those with common brain diseases. A diagnosis of PD had a significant negative association with colds. The incidence of colds was lower in PD than in the other common brain diseases. Physiological alpha-synuclein may contribute to inflammatory responses against infections.